Crossing the Limit Towards Deep UV. Issue 1 (15th April 2013) - Orthaus, Sandra; König, Marcelle; Schönau, Thomas; Buschmann, Volker; Tannert, Sebastian; Lauritsen, Christian; Koberling, Felix; Ortmann, Uwe; Erdmann, Rainer
Abstract Confocal microscopy allows for various fluorescence applications that have found their way into modern biology and medicine leading to new insights into morphology, physiology as well as pathological alterations. Common microscopical analyses include labeling of the sample with extrinsic fluorophores because DNA, saccharides, lipids, membranes, and most cellular structures are non‐fluorescent.